A METHODOLOGICAL FRAMEWORK FOR THE STUDY OF URBAN SPACES IN PERIPHERAL COUNTRIES. -IN TIMES OF NEO-LIBERAL GLOBALIZATION AND TAKING A CRITICAL APPROACH - Arrieta-Chavarría, Omar (2013)
This essay presents some introductory notes within a methodological theoretical framework from a critical approach to the study of urban space in cities on the periphery of the processes of capital accumulation on a global scale, in the context of neoliberal capitalism and its crisis. The essay highlights some of the variables that explain structural and coincidentally forms, which in these cities is urban space, and how we study these from a Marxist geography standpoint and the approach to critical complexity.